A Comparative Study on Subtractive Manufacturing and Additive Manufacturing. (15th April 2022) - Sathish, K.; Kumar, S. Senthil; Magal, R. Thamil; Selvaraj, V.; Narasimharaj, V.; Karthikeyan, R.; Sabarinathan, G.; Tiwari, Mohit; Kassa, Adamu Esubalew
Abstract : In recent days, additive manufacturing (AM) plays a vital role in manufacturing a component compared to subtractive manufacturing. AM has a wide advantage in producing complex parts and revolutionizing logistics panorama worldwide. Many researchers compared this emerging manufacturing methodology with the conventional methodology and found that it helps in meeting the demand, designing highly complex components, and reducing wastage of materials, and there are a wide variety of AM processes. The process of making the components in full use of technology with several manufacturing applications to meet the above is studied along with the properties of AM, and subsequently, the advantages of AM over the subtractive methods are described. In this paper, the achievements in this manner with considerable gains are studied and are concluded as a paradigm shift to fulfil the AM potential.